Konsep Sukuk Wakaf dalam Perspektif Fatwa DSN-MUI - Selamet Hartanto; Devid Frastiawan Amir Sup (Muslim Heritage, 2021)
AbstractFor Muslims in Indonesia, the basic concept of waqf in Islam has been known for a long time, and more than that, in practice if it is explored further, there will be many waqf assets in Indonesia. However, there are still many waqf assets that have not been maximally managed which have the potential to be productive so that more benefits (maslahah) can be obtained. One way of developing these waqf assets is through waqf sukuk. In Indonesia, the provisions of the waqf sukuk are based on the Fatwa DSN-MUI. This study aims to describe the concept of sukuk waqf in the perspective of Fatwa DSN-MUI. This study used a qualitative-descriptive-literature method with the Fatwa DSN-MUI as the main subject of this study. The conclusion, the issuance of sukuk may only be based on the benefits of waqf assets and business activities on waqf assets, while waqf assets cannot be used as the basis for issuing sukuk. The schemes of ‘aqd used in the issuance of waqf sukuk are mudharabah, ijarah, wakalah bil al-istitsmar, musyarakah, or other ‘aqd in accordance with sharia principles. AbstrakBagi umat Muslim di Indonesia, konsep dasar wakaf di dalam Islam sudah sangat mendalam dipahami, dan lebih dari itu, dalam praktiknya jika ditelusuri lebih jauh maka akan banyak ditemukan aset-aset wakaf di Indonesia. Namun demikian, masih banyak aset wakaf yang belum maksimal pengelolaannya yang sebenarnya dapat lebih diproduktifkan lagi sehingga menghasilkan kemaslahatan yang lebih besar. Salah satu cara pengembangan aset wakaf tersebut adalah melalui sukuk wakaf. Di Indonesia ketentuan sukuk wakaf didasarkan kepada Fatwa DSN-MUI. Penelitian ini bertujuan untuk mendeskripsikan konsep sukuk wakaf dalam perspektif Fatwa DSN-MUI. Penelitian ini menggunakan metode kualitatif-deskriptif-kepustakaan dengan Fatwa DSN-MUI sebagai bahan utama kajiannya. Kesimpulan yang didapat, penerbitan sukuk hanya boleh didasarkan kepada manfaat aset wakaf dan kegiatan usaha pada aset wakaf, sedangkan aset wakaf tidak boleh dijadikan dasar penerbitan sukuk. Skema akad yang digunakan dalam penerbitan sukuk wakaf adalah akad mudharabah, ijarah, wakalah bil al-istitsmar, musyarakah, atau akad lain yang sesuai dengan prinsip syariah.